THE INFLUENCE OF GREEN ENTREPRENEURSHIP AND GREEN PRODUCT INNOVATION ON THE PURCHASE INTEREST OF GENERATION Z CONSUMERS - Achmad Basofitrah; Sudarmiatin Sudarmiatin; Naswan Suharsono; Puji Handayati (JURNAL PROFIT, 2025)
This study aims to examine the influence of Green Entrepreneurship and Green Product Innovation on Purchase Intention among Generation Z consumers in Malang City. A quantitative approach with a cross-sectional survey design was employed. Data were collected using a structured Likert-scale questionnaire and obtained from Generation Z respondents selected through purposive sampling. The data were analyzed using SPSS, including validity and reliability testing, normality testing, multicollinearity assessment, and multiple linear regression to test the research hypotheses. The results indicate that Green Entrepreneurship has a positive and significant effect on Purchase Intention. Similarly, Green Product Innovation demonstrates a significant contribution to increasing consumers’ intention to purchase environmentally friendly products. These findings highlight that sustainable entrepreneurial practices and eco-friendly product innovations enhance young consumers’ interest in UMKM products, emphasizing the strategic importance of sustainability in contemporary marketing.